Looking through their eyes: a case study and SWOT analysis of participant-driven videography to inform park research and management - Rogowski, Julianna (Kansas State University, 2021)
Participant-driven videography (PDV) may be a useful tool in park and protected areas (PPA) research. PDV consists of participants employing a camera to record videos about a subject or experience, giving the participant control over what sites are documented and their narration of in situ experience. Given the limited application of PDV to PPA research, this study demonstrates 1) the application of PDV in a multi-case study to explore its’ utility for a qualitative understanding of stakeholder perspectives of visitor experiences, and 2) recommendations for future application of PDV in PPA research. PDV interviews were conducted with a remote video conferencing application with knowledgeable park stakeholders at two NPS units: Rock Creek Park and Chesapeake & Ohio Canal National Historical Park, where the researcher asked stakeholders to conduct a “virtual tour” while identifying areas and attributes of importance. Stakeholders were chosen based on their in-depth knowledge about past and present aspects of the park, experiences which would inform their ideas around future direction. Analysis includes a priori coding of videos and transcripts to highlight variables of importance. SWOT analysis of PDV includes exploring strengths, weaknesses, opportunities, and threats of applying PDV, in this adapted remote environment, to PPA research. Results indicate a wide array of variables past, present, and future that influence visitor experiences, and that PDV offers more strengths than weaknesses in its application, thus we conclude that PDV is a useful tool for gaining rich qualitative insights about PPA ‘s above and beyond more common qualitative approaches.
Keywords: Participant-driven videography; Visitor use management; Visitor experience; National parks; Video methods; Parks and protected areas